High-performance single-photon generation with commercial-grade optical fiber - Soeller, C; Cohen, O; Smith, B; Walmsley, I; Silberhorn, C (2011)
High-quality quantum sources are of paramount importance for the implementation of quantum technologies. We present here a heralded single-photon source based on commercial-grade polarization-maintaining optical fiber. The heralded photons exhibit a purity of at least 0.84 and an unprecedented heralding efficiency into a single-mode fiber of 85%. The birefringent phase-matching condition of the underlying four-wave mixing process can be controlled mechanically to optimize the wavelength tuning needed for interfacing multiple sources, as is required for large-scale entanglement generation. © 2011 American Physical Society.